Neuropsychiatric symptoms in early stage autosomal dominant and sporadic Alzheimer's disease: Neuropsychiatry and behavioral neurology/Mild cognitive impairment/Early symptomatic disease. (7th December 2020) - Pawar, Sanjay; Montoya, Lucy; Barrera, Lillibeth; Mora, Livier; Cortez‐Sanchez, Kristyan; Brook, Jenny; Ringman, John M.
Abstract: Background: Neuropsychiatric symptoms (NPS) in AD, though more prevalent and severe in advanced disease, can occur as early features, with case reports suggesting more robust NPS in autosomal dominant Alzheimer disease (ADAD). The characterization of NPS in person with ADAD and their comparison to late‐onset Alzheimer's disease (LOAD) enhances our ability to anticipate such symptoms and provides insight into differences in the underlying pathology of the two forms of the disease. Method: Informants of 19 participants with mutations known to cause ADAD (mean age 45.58, 36.8% male) and 115 participants with LOAD (mean age 74.71, 42.6% male) were administered the full Neuropsychiatric Inventory (NPI) to assess the presence, frequency, and severity of 12 NPS, namely delusions, hallucinations, agitation, depression, anxiety, elation, apathy, disinhibition, irritability, aberrant motor behavior, sleep, and eating disorders. All participants had Clinical Dementia Rating (CDR) scores of 0.5. Chi‐square tests were used to compare the prevalence of NPS between ADAD and LOAD patients using both NPI screening and subquestions. Result: ADAD and LOAD groups did not significantly differ in terms of MMSE score, CDR Sum of Boxes, gender, or years of education though ADAD subjects were more likely to be of Latinx origin (84% vs. 23%, p<0.001). ADAD and LOAD subjects did not differ on any qualifying questions, except for apathy, which was more common in ADAD mutation carriers (20.9% of LOAD subjects vs. 44.4% of ADAD subjects, p=0.039). Positive responses to subquestions regarding whether the participant was less affectionate and less interested in family were more commonly endorsed in ADAD. Conclusion: Although apathy was more prevalent in ADAD subjects, the difference was not large and was not maintained when controlling for multiple comparisons. We therefore failed to identify robust differences in NPS between ADAD and LOAD. Our findings are limited by the small sample size of ADAD subjects but suggest that NPS are not markedly different in the early stages of ADAD and LOAD.